Process damping technique for aluminium alloy at low speed machining - Mohd Azfadir, Mat Daud (2012)
This thesis investigated the process damping performance of tools when machining aluminium alloy at low speed. The objective of this thesis is to prepare the aluminum alloy workpiece for cutting experiment. Second objective of this project is machining the aluminium alloy workpiece with process damping technique which is using high axial depth of cut and low radial depth of cut. The third objective is to compare process damping performance between three different helix tools. The thesis implants process damping techniques to investigate the fatigue process damping performance between tool types. All tools used in this project are uniform helix tools which represent by solid carbide tool, high speed steel coated tool and solid carbide coated tool. By performing machining which is milling process on CNC Haas VF6 vertical milling machine, data for process damping performance is recorded. From the data, process damping wavelength will be calculated for the comparison of performance. The result obtained indicated that the solid carbide tool have the lowest process damping wavelength while high speed steel coated tool have higher process damping wavelength than solid carbide coated tool. The highest process damping wavelength goes to solid carbide coated tool. As a conclusion, solid carbide coated gave the best performance of machining aluminium alloy at low speed.